PO.3.55 Estimation of cardiovascular risk among SLE patients: analysis from a monocentric cohort. (27th September 2022) - Santangeli, R; Montozzi, G; Gamba, L; Salvucci, S; Manfredi, L; Moroncini, G
Abstract : Purpose: Systemic Lupus Erythematosus (SLE) is an heterogeneous systemic autoimmune disease. Cardiovascular (CV) involvement is one of the most important, linked to an increased morbidity and mortality. Considering only the traditional CV risk factors and scores, the real risk of CV events is underestimated. There is a growing need to elaborate new CV scores and to identify subgroups of patients with a major CV risk1. Methods: We describe our population of SLE patients, in which we analyze the distribution of traditional CV risk factors and scores using V-Cramer and Fisher's exact test p value. We have 43 patients with CV risk factors (38 female and 5 male), with mean age of 52.69 (± 14.42) years (from 18 to 76 years old) and mean disease duration of 13 years. 32.5% of patients have a renal involvement, 55.8% a cutaneous involvement, 72% an articular involvement and 11.6% with a known cardiac involvement. Results: In our cohort 48.8% of patients was a smoker. No correlation was found between smoke and organ involvement, but there is an inverse correlation with antiphospholipid (APL) immunity (v cramer 0.44, fisher's exact test p value 0.005): 75% of patients with APL immunity do not smoke. No correlation was found between dyslipidemia or hypertension and organ involvement, duration of steroid-therapy major of 5 years or CV events, instead there is a correlation between diabetes mellitus and cardiac involvement (V cramer 0.47, Fisher's exact test p-value 0.03). We also analyzed the distribution of Modified Framingham' score and QRisk3 score, but no correlation with organ involvement or CV events was found. Conclusions: Our analysis confirm that considering only traditional CV risk factors is not adequate to estimate real CV risk among SLE patients and that there is a lack of suitable scores. In our department, we have decided to refer our patients to a team of specialized cardiologists in order to identify patients with an increased CV risk and to perform a tight follow – up. References: Drosos GC, et al. Ann Rheum Dis 2022;0 :1–12. doi:10.1136/annrheumdis-2021-221733